THE DESCRIPTION OF PARENTS’ PSYCHOLOGICAL CONDITIONS IN ACCOMPANYING CHILDREN TO LEARN DURING THE IMPLEMENTATION OF STUDY FROM HOME (SFH) IN MAKASSAR CITY AND GOWA REGENCY - Dewi, Eva Meizarra Puspita; Damayanti, Eka; Halimah, Andi; Jalal, Novita Maulidya (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: This study aims to investigate the psychological conditions of parents in assisting children in learning during the implementation of Study from Home (SFH) in Makassar City and Gowa Regency. This study used quantitative survey research. The samples were 159 parents who were selected by random sampling. The instrument used was a questionnaire containing closed, semi-closed, and open-ended questions distributed using Google forms. The collected data were analyzed using descriptive statistics. The results showed that parents considered SFH as a moment to accompany and be closer with their children. The parents' perception of online learning was less effective (36.8%) for their children because of limited internet access (57.9%), many distractions from home (34%), and the parents did not understand the matter (17.6). The children’s complaints during SFH were: not being able to play and do homework in groups (37.1%), lot of tasks (homework) (32.1%), preferred taught by teachers directly (29.6%) and felt bored (29.6%). The parents perceived SFH as follows; feeling comfortable with family (62.9%), bored with routine (31.4%), increased workload (18.9%). However, the physical complaints were less because the parents’ role was powerful in accompanying the children during SFH. Moreover, the family harmony increased with this moment. This study recommends that parents continue the habits to assist children in learning. Abstrak: Tujuan dari penelitian ini adalah untuk memperoleh gambaran kondisi psikologis orang tua saat mendampingi anak belajar selama Study from Home (SFH) di Kota Makassar dan Kabupaten Gowa. Penelitian ini merupakan penelitian kuantitatif jenis survey. Jumlah sampel yakni 159 orang tua yang terpilih secara random sampling. Pengumpulan data menggunakan kusioner yang berisi pertanyaan tertutup, semi tertutup dan pertanyaan terbuka yang disebarkan menggunakan google formulir. Data yang terkumpul dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa SFH dimaknai oleh orang tua sebagai moment untuk mendampingi dan lebih dekat dengan anak. Orang tua merasakan metode daring kurang efektif (36,8%) bagi anaknya, sebab: akses internet yang terbatas (57,9%), banyak gangguan dirumah (34%), dan orangtua tidak memahami materi pelajaran anak (17,6). Keluhan yang dirasakan oleh anak selama SFH adalah: tidak bisa bermain dan kerja kelompok (37,1%), banyak tugas (32,1%), lebih suka guru yang ajar (29,6%), dan bosan (29,6%). Adapun orangtua memaknai SFHberupa; perasaan nyaman dengan keluarga (62,9%), bosan dengan rutinitas (31,4%), beban kerja bertambah (18,9%). Namun demikian, keluhan fisik tidak terlalu dirasakannya karena peran orangtua sangat kuat dalam mendampingi keluarga selama SFH, bahkan merasa bahwa dengan moment ini keharmonisan keluarga menjadi meningkat. Oleh karena itu direkomendasikan bagi orangtua untuk meneruskan kebiasaan yang sudah terbentuk yakni mendampingi anak belajar.